Complete heart block: an atypical presentation with an atypical diagnosis - Mishra, Vikas; Chatterjee, Trisha; M., Chandramouli (International Journal of Research in Medical Sciences, 2023)
Congenital heart block is frequently associated with underlying structural congenital heart disease or connective tissue disorders. Neonatal lupus is considered a form of passively acquired autoimmune disease in which maternal autoantibodies, namely, anti-Ro and anti-La, cross the placenta and injure the previously normal fetal heart. Here, a young female, 30 years of age, who presented with atypical cardiac manifestations, was diagnosed with complete heart block. She was evaluated thoroughly for its etiology, including structural, medication, infective, thyroid and autoimmune panel. Antinuclear antibody (ANA) was positive by immunofluorescence method with 1:160 titre and with fine speckled pattern. Anti-SSA/Ro antibody was positive with a titre of 30.20 units. Anti-Smith antibody was also reported to be positive. On further investigations, her mother also had positive ANA by Immunofluorescence method with a titre of 1:80, with anti dsDNA, anti Ro/SSA, anti La/SSB positivity. The patient was thus diagnosed as a case of lupus causing her to present with complete heart block in adulthood. Patient was managed with TPI followed by PPI and was discharged with no complications. Neonatal lupus can cause heart block of varying degrees that may be noted in utero presenting as congenital heart block. SLE presenting as congenital heart block in young adults is a rare finding. This case report reviews an adult female of SLE presenting to the emergency for the first time with atypical cardiac manifestations and diagnosed as a case of congenital heart block with laboratory investigations revealing lupus as the primary etiology.